Subsurface Structure and Fluid Flow Analysis Using Geophysical Methods in the Geothermal Manifestation Area of Paguyangan, Brebes, Central Java - Setyawan, Agus; Triahadini, Agnis; Yuliananto, Yayan; Aribowo, Yoga; Widiarso, Dian Agus (International Journal of Renewable Energy Development, 2016)
The indication of an active geothermal system is shown by the presence of surface manifestations such as the hot spring in Kedungoleng, Paguyangan, Brebes, Central Java. The temperature of the largest hot spring reaches 74o C and there is an assumption that this is an outflow of Mount Slamet geothermal system. DC-resistivity, Spontaneous Potential (SP) and Shallow Surface Temperature surveys were conducted to determine the subsurface structure as well as its correlation with the distribution of thermal fluid flow and shallow surface temperature. The subsurface resistivity has been investigated using 5 points of the Schlumberger configuration with 400 m separation for each point. For the fluid and temperature pattern, a measurement using 15 m interval in 3 lines of conducting fixed electrode configuration has been carried out, along with a 75 cm of depth of temperature measurement around the manifestation area. The thermal fluid is assumed by the low resistivity of 0.756 to 6.91Î©m and this indicates sandstone that has permeable characteristic. The fluid flows in two layers of Sandstone at more than 10 meter from surface of the first layer. Accordingly, the SP values have a range between -11- 11 mV and a depth interval of 13.42- 28.75 m and the distribution of temperature is between 24o-70oC at a tilting range of 46.06o-12.60o. Hence it can be inferred that the thermal fluid moves in the Northwest direction and is controlled by a fault structure stretching from Northwest to Southeast.Article History: Received Feb 3, 2016; Received in revised form July 11, 2016; Accepted August 13, 2016; Available onlineHow to Cite This Article: Setyawan, A., Triahadini, A., Yuliananto, Y., Aribowo, Y., and Widiarso, D.A. (2016) Subsurface Structure and Fluid Flow Analyses Using Geophysical Methods in Geothermal Manifestation Area of Paguyangan, Brebes, Central Java. Int. Journal of Renewable Energy Development, 5(3), 171-177.http://dx.doi.org/10.14710/ijred.5.3.171-177